Causes and Characteristics of Death in Intensive Care Units: A Prospective Multicenter Study. (May 2017) - Orban, Jean-Christophe; Walrave, Yannick; Mongardon, Nicolas; Allaouchiche, Bernard; Argaud, Laurent; Aubrun, Frédéric; Barjon, Geneviève; Constantin, Jean-Michel; Dhonneur, Gilles; Durand-Gasselin, Jacques; Dupont, Hervé; Genestal, Michèle; et al.
Abstract : Background: Different modes of death are described in selected populations, but few data report the characteristics of death in a general intensive care unit population. This study analyzed the causes and characteristics of death of critically ill patients and compared anticipated death patients to unexpected death counterparts. Methods: An observational multicenter cohort study was performed in 96 intensive care units. During 1 yr, each intensive care unit was randomized to participate during a 1-month period. Demographic data, characteristics of organ failures (Sequential Organ Failure Assessment subscore greater than or equal to 3), and organ supports were collected on all patients who died in the intensive care unit. Modes of death were defined as anticipated (after withdrawal or withholding of treatment or brain death) or unexpected (despite engagement of full-level care or sudden refractory cardiac arrest). Results: A total of 698 patients were included during the study period. At the time of death, 84% had one or more organ failures (mainly hemodynamic) and 89% required at least one organ support (mainly mechanical ventilation). Deaths were considered unexpected and anticipated in 225 and 473 cases, respectively. Compared to its anticipated counterpart, unexpected death occurred earlier (1 day vs. 5 days; P < 0.001) and had fewer organ failures (1 [1 to 2] vs. 1 [1 to 3]; P < 0.01) and more organ supports (2 [2 to 3] vs. 1 [1 to 2]; P < 0.01). Withdrawal or withholding of treatments accounted for half of the deaths. Conclusions: In a general intensive care unit population, the majority of patients present with at least one organ failure at the time of death. Anticipated and unexpected deaths represent two different modes of dying and exhibit profiles reflecting the different pathophysiologic underlying mechanisms. Abstract : In a general intensive care unit population, the majority of patients present with at least one organ failure at the time of death. Compared to its anticipated counterpart, unexpected death occurred earlier and had fewer organ failures.